Prognostic value of minimal residual disease in acute lymphoblastic leukaemia in childhood - Van Dongen, Jacques J. M.; Seriu, Taku; Panzer-Grümayer, E Renate; Biondi, Andrea; Pongers-Willemse, Marja J; Corral, Lilly; Stolz, Frank; Schrappe, Martin; Masera, Giuseppe; Kamps, Willem A; Gadner, Helmuth; van Wering, Elisabeth R; et al. (The lancet, 1998)
Background - Sensitive techniques for detection of minimal residual disease (MRD) at degrees of one leukaemic cell per 103-106 cells (10−3-10−6) during follow-up of children with acute lymphoblastic leukaemia (ALL) can provide insight into the effectiveness of cytotoxic treatment. However, it is not yet clear how information on MRD can be applied to treatment protocols. - Methods - We monitored 240 patients with childhood ALL who were treated according to national protocols of the International BFM Study Group. 60 patients relapsed and the patients in continuous complete remission (CCR) had a median event-free follow-up of 48 months. Bone-marrow samples were collected at up to nine time points during and after treatment. Standardised PCR analysis of patient-specific immunoglobulin and T-cell receptor gene rearrangements and TAL1 deletions were used as targets for semiquantitative estimation of MRD. Amount of MRD was classed as 10−2 or more, 10−3, and 10−4 or less. - Findings - MRD negativity at the various follow-up times was associated with low relapse rates (3-15% at 3 years), but five-fold to ten-fold higher relapse rates (39-86% at 3 years) were found in MRD-positive patients. The distinct degrees of MRD appeared to have independent prognostic value (p [trend]<0·001) at all separate time points, especially at the first two time points (at the end of induction treatment and before consolidation treatment). At these two time points a high degree of MRD (≥10−2) was associated with a three-fold higher relapse rate when compared with patients with a low degree of MRD (≤10−4). At later time points (including the end of treatment) even a low degree of MRD was associated with a poor outcome. Positivity in patients in CCR after treatment was rare (<1%). With the combined MRD information from the first two follow-up time points, it was possible to recognise three different risk groups—55 (43%) were in a low-risk group and had a 3-year relapse rate of only 2% (95% Cl 0·05-12%); 19 (15%) were in a high-risk group and had a relapse rate of 75% (55-95%); and 55 (43%) were in an intermediate-risk group and had a 3-year relapse rate of 23% (13-36%). - Interpretation - Our collaborative MRD study shows that monitoring patients with childhood ALL at consecutive time points gives clinically relevant insight into the effectiveness of treatment. Combined information on MRD from the first 3 months of treatment distinguishes patients with good prognoses from those with poor prognoses, and this helps in decisions whether and how to modify treatment.
Online verfügbar 22. Dezember 1998
Gesehen am 04.01.2024